Pengaruh Program Pengembangan UMKM Terhadap Pertumbuhan Usaha di Kecamatan Kebomas Kabupaten Gresik - Ghina Muzakhi Gresita Putri; Tjitjik Rahaju; Indah Prabawati; Firre An Suprapto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the impact of the Micro, Small, and Medium Enterprise (MSME) Development Program on business growth in Kebomas District, Gresik Regency. MSMEs play a vital role in the Indonesian economy but often face challenges regarding access to finance, marketing, and legal compliance. This study employs a quantitative approach using a survey method targeting MSME owners in Kebomas District. The results indicate that the MSME Development Program has a positive and significant influence on business growth in Kebomas District. Specifically, the MSME Development Program variable contributes 69.4% to business growth, indicating that government intervention has a tangible impact. However, the remaining 30.6% of business growth is influenced by factors outside the scope of this study, such as macroeconomic conditions, market competition, and the internal characteristics of the MSMEs. The most prominent program indicators are those related to legal and marketing aspects (ease of obtaining NIB and halal certification) and digitalization, which effectively expand market reach and increase sales. Meanwhile, increased sales and market reach are the dimensions of business growth that show the greatest responsiveness, whereas workforce expansion shows the slowest response. The study concludes that the MSME Development Program in Kebomas has successfully created a conducive ecosystem, though it still requires strengthening in terms of profit enhancement and labor absorption.